Pattern of developmental sex disorders in a tertiary hospital in Sudan - Ali, Hussein Abdalla M.; Alawad, Awad; Ali, Abdelbassit S.; Abdalla, Ahmed Abd Elrahman (International Journal of Medicine, 2014)
Background: Disorders of sex development (DSD) comprise a group of congenital conditions characterized by atypical chromosomal, gonadal, and anatomic sex development. The birth of a child with these disorders considered a medical and psychosocial emergency. Objective: The aim of this study was to see the prevalence, etiological factors, management, and problems faced in handling these cases. Methods: This is a descriptive retrospective study was conducted at Soba university hospital including all patients with proved DSD over a 6-year period. Results: One hundred thirty-six cases were seen, of which 40 were included in the study. The median age at presentation was 3 years. The most common cause of XX DSD was congenital adrenal hyperplasia (72.5%) and that of XY DSD was androgen insensitivity syndrome. Eleven patients (27.5 %) needed sex reassignment. There was a preference for the male sex. Conclusion: DSDs are not uncommon in Sudan. Because of lack of awareness and sociocultural reasons cases are referred late. Multidisciplinary teams have to be trained to make services accessible and affordable.   Keywords: Children; Disorders of Sex Development; Sudan.